EPIDEMIOLOGI DETEKSI DINI PENYAKIT TIDAK MENULAR DI DESA MULIOREJO - Dame Evalina Simangunsong; Marlisa; Yulina Dwi Hastuty; Elkadi (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2026)
Noncommunicable diseases (NCDs) are the leading cause of death in Indonesia and continue to show an upward trend, especially among adults. Obesity, hypertension, hyperglycemia, dyslipidemia, and unhealthy behaviors contribute to the high burden of NCDs. Early detection of risk factors is an important strategy in the prevention and control of NCDs. This study aims to analyze the characteristics and prevalence of NCD risk factors. This study uses a descriptive design with a cross-sectional design. The sample size is 34 respondents aged 25 years. Data collection was conducted through anthropometric measurements (Body Mass Index and waist circumference), blood pressure, fasting blood sugar, total cholesterol, uric acid, and interviews related to behavioral risk factors (physical activity, fruit and vegetable consumption, history of NCDs, alcohol consumption, and exposure to cigarette smoke). Data analysis was performed univariately using frequency distribution and percentages. There were 85.3% of respondents in the pre-obesity to obesity category. It was found that 50% of respondents had grade I and II systolic hypertension and 35.3% were in the pre-hypertension category. A total of 29.4% had fasting blood sugar levels >200 mg/dL. A total of 64.7% had borderline to high cholesterol levels. A total of 44.1% had a history of NCDs, with a family history of 29.4% and exposure to cigarette smoke of 38.2%. Most respondents had significant risk factors for NCDs, particularly obesity, hypertension, and dyslipidemia. There is a need to strengthen community-based early detection and promotive-preventive intervention programs to reduce the risk of NCDs.